AN ANALYSIS OF VETERAN INDIAN ARTISTS’ CREATIONS; THROUGH VISUAL NARRATION - Gupta, Shatrudhan Kumar (International Journal of Research -GRANTHAALAYAH, 2025)
Indian arts have been deeply connected with roots since ancient times. Art created by Indian artists is profoundly and significantly visualized through visual narrative with various art mediums. This research study provides an introduction of selected veteran Indian artists and examines their creative practices and inspirations as well the research paper analyses selected artists’ creations through visual narrations and attempts to give an aesthetic understanding of the language of visuals.